Pentingnya Transparansi dan Akuntabilitas Laporan Keuangan Dana Zakat Infaq dan Shadaqoh terhadap Kepercayaan Pembayar Zakat, Infaq, Shadaqoh di LAZISMU DIY - Urwahni Aprita Sandy; S Sumaryanto (SAFE-Network, 2023)
Factors that affect trust are transparency and accountability as a form of accountability for the amil zakat institution in holding the mandate entrusted by zakat payers, infaq, alms. Meanwhile, in building trust, there needs to be transparency and accountability so that financial information is conveyed in an open, trustworthy, accurate and reliable manner. The aim of the research is to know the forms of transparency and accountability in the management of zakat, infaq & sedekah. The research method uses quantitative empirical analysis to analyze the level of trust of zakat, infaq, alms payers based on transparency and accountability. This study uses primary data through the answers of respondents in a structured way in the form of a questionnaire. Meanwhile, data analysis techniques use multiple regression analysis through the t test, F test and test the coefficient of determination. The results of the research on testing the hypothesis that the variables transparency (X1), accountability (X2) have an influence on the trust payers of zakat, infaq, alms (Y) and simultaneously there is a significant effect on the variables of trust payers of zakat, infaq, alms (Y). Transparency and accountability in financial reports have an influence on the level of trust of zakat, infaq, alms payers in the amil zakat infaq sedekah Muhammadiyah Institution in the 2021-2023 period. Thus, all types of programs and distribution can be carried out transparently, right on target and known by other parties. The implication of this research is to be able to carry out further research to see the level of trust of zakat, infaq, alms payers in the following year. As well as the places that are the subject of research are not only at the Amil zakat infaq alms Muhammadiyah Institute.